Análise da produtividade com auxílio do indicador RUP em uma obra de alvenaria estrutural: um estudo de caso - MENDONÇA, Heitor Queiroz de (2024)
The study of productivity in the civil construction industry plays a crucial role in the sector's development and improvement. In this research, productivity was addressed through the RUP indicator (Unitary Production Ratio), focusing on four types of rough construction services: structural masonry, veneer masonry, screed, and internal plastering. The aim was to analyze productivity in specific rough construction services using the RUP indicator, examining the causes responsible for their variations, and comparing the values obtained with those provided by the budgetary basis of the company executing the construction. It was concluded that, even with the learning effects of the teams, a variety of causes must be anticipated by the internal management of the construction site during planning and scheduling. This preventive approach aims to mitigate potential obstacles during the execution of services, contributing to the efficiency and success of the construction project in the civil engineering sector.